Assessing Financial Sustainability of Community Network Project through e3value Modelling and Simulation - Cheah, Wai Shiang; Chong, Xing Zi; Muhammad Asyraf, Khairuddin; Nurfauza, Jali; Rahmat, Hidayat (Joiv, 2020)
Many efforts had been done to make ICTs available in rural area to increase their incomes and productivities. For example, a community ecommerce is introduced to promote community handicraft and income generation; other projects like deploying VSAT to improve the internet connectivity at rural area. Although the project is developed, it is facing a challenge like how to sustain the ICT4D projects? This paper presents the study of financial sustainability of community network project through e3value modelling and simulation. Financial sustainability is one of the important factor for community projects. As a NGO or researcher that is trying to help the community, is it possible for us to access the feasibility of any projects for communities so that a realistic suggestion or proposal can be planned? To sustain the community commerce, it cannot be denied that a well planning and measurement on financial sustainability of the projects is required. Hence, we believe that e3value can be used as a tool to measure the financial sustainability of community network projects. With the use of 3value model, it can serve as a reference for various parties in resolving the financial sustainability issue.